A responsive governance path to health equity: the role of state-led public interest litigation in China - Qi, Fei; Yu, Bin (Frontiers in Public Health, 2025)
Against the backdrop of the “Healthy China 2030” strategy, this paper examines China's unique Public Interest Litigation (PIL) system as an emerging and critical mechanism for safeguarding the health rights of vulnerable populations. The central thesis of this paper is that China's PIL should be understood not as a conventional rights-remedy instrument, but as a state-led innovation in “responsive governance.” This system, with the public procuratorate as its core actor, establishes an internal feedback loop designed to identify and rectify administrative regulatory failures, primarily through its pre-litigation procedures. The research finds that this system protects health rights through two distinct pathways: first, by providing universal, indirect protection through the regulation of social determinants of health, such as environmental quality and food safety; and second, by offering targeted, direct protection for specific groups, addressing issues like occupational health for migrant workers and accessibility of services for persons with disabilities. Through a systematic comparative analysis with the models of India (society-driven mobilization), South Africa (constitutional adjudication), and Brazil (individual rights realization), this paper illuminates the distinctiveness of the Chinese model. Its objective is focused on procedural administrative correction and enhancing governance efficacy, rather than on fundamental policy challenges. Although constrained by factors such as state-led agenda-setting, the model's emphasis on collective interests and systemic risks may generate more broadly shared public health benefits. This analysis provides a unique institutional case study on enhancing state governance capacity in the public health domain and contributes a nuanced perspective to global discussions on law, governance, and health equity.